Contribution of Neurons and Glial Cells to Complement-Mediated Synapse Removal during Development, Aging and in Alzheimer’s Disease - Celia Luchena; Jone Zuazo-Ibarra; Elena Alberdi; Carlos Matute; Estibaliz Capetillo-Zarate (Mediators of Inflammation)
Synapse loss is an early manifestation of pathology in Alzheimer’s disease (AD) and is currently the best correlate to cognitive decline. Microglial cells are involved in synapse pruning during development via the complement pathway. Moreover, recent evidence points towards a key role played by glial cells in synapse loss during AD. However, further contribution of glial cells and the role of neurons to synapse pathology in AD remain not well understood. This review is aimed at comprehensively reporting the source and/or cellular localization in the CNS—in microglia, astrocytes, or neurons—of the triggering components (C1q, C3) of the classical complement pathway involved in synapse pruning in development, adulthood, and AD.